Socio-Urban integration in Argentinean Patagonia: Material production and experiences - Ferrari, Paula (2021)
Starting in 1970, the city of Puerto Madryn –located in the Argentinian Patagonia- has experienced a major surge of urban and demographic growth. This expansion has been accompanied by certain urban development practices which have resulted in severe inequalities in the access to land and housing. In turn, this had the effect of worsening both social territorial and social urban segregation. The Nueva Chubut neighborhood is a product of the above developments. This article analyzes the socio urban integration of this low income quarter. Due account is given to the material production and the experiences of its inhabitants. Based on stories about practices and meanings associated with place, an attempt is made to understand how the integration of social groups to the neighborhood is achieved. Two major categories are employed in this exploration: the material scaffolding supporting this integration, and the feelings of belonging associated to the social bonds that link the local community to the rest of the city. The research uses a qualitative exploratory design, based on bibliographical research, the investigation of legal norms and in-depth interviews with residents and neighborhood leaders. Results reveal that a full and effective integration of the quarter is far from accomplished. The inhabitants themselves, their struggles and practices in everyday life, are the main driving force of this incorporation. These practices pave the way for the recognition of previously neglected citizen rights, such as the right to a decent habitat.